Leitura e semiótica: uma análise acerca dos marcadores sociais da diferença e imagens de controle em livros didáticos de língua portuguesa - Duarte, Fabíola Jerônimo (2023)
As recognize that we are experiencing a mass propagation of signs, including in educational contexts and that in many cases, aim to construct meanings that reinforce the differences between subjects, especially when these differences are operationalized based on race, we propose to investigate the presence of social markers of difference and controlling Images in the Portuguese language collection “Tecendo Linguagens” proposed for Elementary School II. As a central objective, we analyze how these social markers of difference and controlling Images articulate implicit and explicit discourses in the material under study and that contribute to the structuring of racism in the educational context, at the same time that we verify how a semiotic approach to these discourses can contribute for the development of a critical reading. With regarding to the methodology, as it is a study focused on education, we choose to carry out a qualitative research basis and inductive method. The action-research was designed for a 9th grade class of Elementary School II at Escola Estadual Profa. Ocila Bezerril, which is located in the city of Montanhas, state of Rio Grande do Norte. Our intervention consisted of applying didactic sequences based on a semiotic approach (Peirce’s semiotics). Concerned the theoretical basis, the research is anchored in the considerations of Santaella (2000, 2002, 2005, 2007), about the semiotics; Collins (2009), Bueno (2020) and hooks (2019), about the concept of Controlling Images and operationalized oppression in relation to black people. With regard to the social markers of difference, we use the contributions of Hirano (2009) and Zamboni (2009) and Hall (2003, 2016) on language as a means of constructing differences through the influence of culture. Finally, as a result of our research, we found that, through the study of the “Tecendo Linguagens” collection, the textbooks favor the logic of domination of groups that historically and culturally use the processes of devaluation over the other, to strengthen the distinctions between subjects and the construction of a social structure in which the subjugated have their lives and identities regulated. Thus, the semiotic approach of such social markers and controlling Images contributed significantly to the understanding of how the meanings we construct, as well as our identities are performed by the social environment, mainly, by the educational context itself. Therefore, we observe that the action we propose was just a crack of resistance that we opened against an immensity of intentionally formulated connotations to cease any and all fronts of social relocation on race. Connotations that we know extend beyond educational contexts, but that through the knowledge that comes from these spaces, can be reduced and disarticulated in the future.